2018
DOI: 10.15448/1984-4301.2017.2.26370
|View full text |Cite
|
Sign up to set email alerts
|

Intralingual subtitles, interlingual subtitles, and video comprehension: insights from an exploratory study

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4. , were equally divided into two experimental groups (intralingual subtitles and interlingual subtitles) and one control group (no subtitles). Participants' performance was measured based on a general and specific video comprehension test. Data were analyzed both quantitatively and qualitatively. Regarding the effects of subtitles on video comprehension, statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Also, learners tend to be better at reading than listening, and they can benefit from seeing difficult content on their native language first (Markham et al, 2001). However, scant exceptions have favored captions (e.g., Hayati & Mohmedi, 2011) and some studies have reported inconclusive or conflicting results depending on learners' proficiency level (e.g., Bairstow & Lavaur, 2011;Guichon & McLornan, 2008;Matielo et al, 2017;Vulchanova et al, 2015).…”
Section: Captions Subtitles and Proficiencymentioning
confidence: 99%
“…Also, learners tend to be better at reading than listening, and they can benefit from seeing difficult content on their native language first (Markham et al, 2001). However, scant exceptions have favored captions (e.g., Hayati & Mohmedi, 2011) and some studies have reported inconclusive or conflicting results depending on learners' proficiency level (e.g., Bairstow & Lavaur, 2011;Guichon & McLornan, 2008;Matielo et al, 2017;Vulchanova et al, 2015).…”
Section: Captions Subtitles and Proficiencymentioning
confidence: 99%
“…Cabe mencionar que, los participantes realizaron mayor número de fijaciones, bien sea en la imagen o en los subtítulos, no solo por cuestiones de dinamismo, sino también porque seleccionaron uno de los dos inputs visuales disponibles (verbal o no verbal) por razones de eficiencia de procesamiento, como lo señala Matielo et al (2018) en su estudio.…”
Section: Discussionunclassified
“…Según un estudio exploratorio de Matielo, de Oliveira & Baretta (2018), se encontró que el contenido subtitulado puede llegar a ser muy enriquecedor, sobre todo para la adquisición de una segunda lengua, en la cual a medida en que esta se desarrolla y se obtienen nuevas habilidades, la dependencia por los subtítulos disminuye. Por otra parte, se señala que la combinación de sonidos e imágenes mejora la relación entre palabras y sus significados, siendo estos a su vez contenido de entretenimiento que logra superar los textos básicos y estáticos, aportando información multisensorial para los distintos tipos de aprendizaje.…”
Section: Anajosé Pardo Díaz Haide Jineth Briceño Suarez Judy Costanza...unclassified
“…Studies on interlingual and intralingual subtitled videos have covered a number of language domains, such as: the improvement of Foreign/Second Language (L2) reading (Markham & Peter, 2003;Kruger & Steyn, 2014), L2 listening comprehension with/without L2 vocabulary learning (Garza, 1991;Huang & Eskey, 1999;Markham, Peter, & McCarthy, 2001;Stewart & Pertusa, 2004;Winke, Gass, & Sydorenko, 2010;Matielo, Oliveira, Baretta, 2017), L2 vocabulary learning (D'Ydewalle & Van de Poel, 1999;Bianchi & Ciabattoni, 2008;Matielo, Collet, & D'Ely, 2013), the effects on implicit and explicit memory and cognitive processing (Bird & Williams, 2002), and the acquisition of L2 grammar (Van Lommel, Laenen, & D'Ydewalle, 2006;Bianchi & Ciabattoni, 2008). Although there is a substantial body of knowledge to date concerning the effects of subtitling on L2 development, very few studies have been carried out with the brazilian population so far.…”
Section: Introductionmentioning
confidence: 99%